Wings of fire. Book five, The brightest night : the graphic novel - Sutherland, Tui, 1978-; Deutsch, Barry; Swirsky, Rachel (Graphix, 2021)
Just when Sunny was ready and willing to try her plan to fulfill the Dragonet Prophecy and end the war, news from the Morrowseer shakes her faith in her destiny. There may never be a SandWing queen again if Sunny cannot recover her faith in herself and her friends.